Estimating Current and Future Groundwater Resources of the Maldives - Bailey, Ryan T. (Wiley, 2016)
The water resources of the atolls of the Republic of Maldives are under continual threat from climatic and anthropogenic stresses, including land surface pollution, increasing population, drought, and sea-level rise (SLR). These threats are particularly acute for groundwater resources due to the small land surface area and low elevation of each island. In this study, the groundwater resources, in terms of freshwater lens thickness, total volume of fresh groundwater, and safe yield are estimated for the 52 most populous islands of the Maldives for current conditions and for the year 2030, with the latter accounting for projected SLR and associated shoreline recession. An algebraic model, designed in previous studies to estimate the lens thickness of atoll islands, is expanded in this study to also estimate volume of groundwater. Results indicate that average current lens thickness, groundwater volume, and per capita safe yield are approximately 4.6 m, 1,300 million liters, and 300 l/day, and that these values will decrease by approximately 10, 11, and 34%, respectively, by the year 2030. Based on results, it is demonstrated that groundwater, in terms of quantity, is a viable source of water for the islands of the Maldives both now and in coming decades, particularly for islands with large surface area and low population. Study results can provide water resource managers and government officials with valuable data for consideration in water security measures. This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions. http://olabout.wiley.com/WileyCDA/Section/id-820227.html